Practical Gas Chromatography - Dettmer-Wilde, Katja (Springer, 2014)
Gas chromatography continues to be one of the most widely used analytical techniques, since its applications today expand into fields such as biomarker research or metabolomics. This new practical textbook enables the reader to make full use of gas chromatography. Essential fundamentals and their implications for the practical work at the instrument are provided, as well as details on the instrumentation such as inlet systems, columns and detectors. Specialized techniques from all aspects of GC are introduced ranging from sample preparation, solvent-free injection techniques, and pyrolysis GC, to separation including fast GC and comprehensive GCxGC and finally detection, such as GC-MS and element-specific detection. Various fields of application such as enantiomer, food, flavor and fragrance analysis, physicochemical measurements, forensic toxicology, and clinical analysis are discussed as well as cutting-edge application in metabolomics is covered. About the Editors: Katja Dettmer-Wilde is Principal Investigator heading the mass spectrometry - metabolomics group at the Institute of Functional Genomics, University of Regensburg, Germany. She studied chemistry at the University of Leipzig and got her PhD with Werner Engewald working on the analysis of volatile organic compounds by GC-MS. Since her postdoctoral studies at the University of California Davis she has been focusing on hyphenated separation techniques in metabolomics. Werner Engewald is professor emeritus of the University of Leipzig, Germany. He is one of the leading gas chromatographers worldwide and has made substantial contributions towards the development of this technique. He regularly gives courses for GC users. He was awarded the Martin gold medal of the Chromatographic Society in 2002 and the Clemens-Winkler-Medal of the Division of Analytical Chemistry of the German Chemical Society in 2009.